Keeping the fires burning: Militarisation and the politics of gender in South Africa - Cock, Jackie (My University, 1987)
This paper focuses on the linkages between women and militarisation. Women are understood as a social category with distinctive and specific experiences. Such experience is structured not only by gender but by other social relations - most importantly those of race and class. Militarisation is understood to mean the mobilisation of resources for war. The process of militarisation is one of the most dramatic characteristics of the contemporary global scene. Militarisation is manifest in sharp increases in military expenditure, in the growing destructive capacity of military weapons, in the spread of the power and influence of the military and in the increasing number of people under arms. This process is evident both in global terms and more specifically in South African society. The linkages between women and the process of militarisation are obscured. They are mystified by two opposing analyses - those of sexism and feminism. Both analyses exclude women from war on the grounds that women are bearers of 'special qualities'. Sexism excludes women from the ranks of the military on the grounds of their physical inferiority and unsuitability for combat roles. One variant of feminism similarly excludes women but on opposite grounds - that of women's innate nurturing qualities, their creativity and pacificism. The outcome of both positions is that war is understood as a totally male affair - the military is a patriarchal institution from which women are excluded, and by whom they are victimised. Women are victims in all wars. Men plan them, they train for them and they conduct them. (As, 1982: 355) However, militarisation - as a global process - is increasingly using women as a military resource. Both manpower constraints and equal rights feminism have contributed to this process. Equal rights feminism has stressed women's rights to achievement, power and opportunity; women's rights to make both money and war. It is argued that equal rights implies equal responsibilities including the obligation of military service. Consequently some equal rights feminists demand the right of women to serve in the armed forces and claim that women are as capable as men for combat roles. A different variant of feminism argues the theme of exclusion; women's capabilities are understood to involve a creativity and nurturance which must be transformed into active support for the peace movement. Their argument is that women especially wives and mothers - have a special concern with peace, with preserving rather than destroying life. This paper attempts to undermine both these positions. It focuses on the connection between women and war, both theoretically and in relation to South African society. It argues that women contribute Keeping the Fires Burning 02. to the militarisation of our society in both material and ideological terms. It attempts to show that these linkages are complex and reverberate with contradictions which are embedded deep in the peculiar social conditions of South Africa. Writing this paper - in the winter of 1987 - it is clear that the apartheid regime faces a major crisis - both in terms of external pressure through sanctions and increasing moves to isloate the regime, and internal pressure through rising black resistance which three states of emergency, large scale detentions and torture have failed to crush. Discontent and anxiety are apparent in all areas of our society. Against this background of pressing external and internal dangers to the regime, the state may introduce the conscription of white women in some form. It thus seems urgent - for both analytical and strategic reasons - to scrutinise the relation between women and militarisation. With this end the paper proceeds in five parts. Part 1 examines militarisation as a contested concept; Part 2 attempts to delineate the militarisation of South African society; Part 3 outlines the different ways of conceptualising the relation between women and militarisation; Part 4 attempts to demonstrate this relation empirically in South Africa; and Part 5 points to some of the contradictions involved. The paper is tentative and exploratory but hopefully suggestive of further debate and research.
African Studies Seminar series. Paper presented October, 1987